Tourism Communication Policy in Sustainable Tourism and Climate Change in Garut Regency - Sunuantari, Manik; Klicek, Tamara (Ikatan Sarjana Komunikasi Indonesia, 2024)
The tourism sector as one of the drivers of the Indonesian economy is also affected by natural and non-natural disasters. Climate change and disasters encourage the government of Garut Regency in West Java, Indonesia, to carry out various tourism communication policies Â as part of the effort to increase sustainable tourism activities in the face of climate change and disasters. This research aims to find a model of sustainable tourism communication policy in the face of climate change in Garut Regency. This research uses symbolic interactionism theory, growth pole theory and Community Based Tourism (CBT). The exchange of symbols between tourism actors will build a common meaning in making sustainable tourism communication policies. The type of research used a case study with a research location in Garut Regency, a tourist site as well as a disaster-prone area. Data collection techniques were carried out through observation, interviews and documentation. Data validity used data triangulation, investigator triangulation, and theory triangulation. The results showed that the policy used in the development of sustainable tourism in Garut Regency emphasizes collaboration and communication of all stakeholders. The involvement of all stakeholders will encourage the realization of community welfare. The focus of sustainable tourism development is the community. Community welfare will be achieved if the community is fully involved in all tourism activities.